2010
DOI: 10.1007/s00339-010-5672-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the residual stress state and microstructure of stainless steel with mechanical surface treatments

Abstract: Four mechanical surface treatments have been considered for the application to austenitic stainless steel structures. Shot peening (SP), laser shock peening (LSP), ultrasonic impact treatment (UIT) and water jet cavitation peening (WJCP), also known as cavitation shotless peening (CSP), have been applied to 8 mm thick Type 304 austenitic stainless steel coupons. This study considers the merits of each of these mechanical surface treatments in terms of their effect on the surface roughness, microstructure, leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 18 publications
3
41
0
1
Order By: Relevance
“…These results agree with the previous studies about the influence of LSP and BB on the residual stress state and work hardening of Ti-6Al-4V [2]. Turski et al [7] compared the efficacy of ultrasonic impact treatment (UIT), LSP and water jet cavitation peening (WJCP) at introducing residual stresses and modifying the near surface state compared to SP benchmark for AISI 304. It was concluded that WJCP and LSP introduced the lowest levels of surface roughening.…”
Section: Introductionsupporting
confidence: 82%
“…These results agree with the previous studies about the influence of LSP and BB on the residual stress state and work hardening of Ti-6Al-4V [2]. Turski et al [7] compared the efficacy of ultrasonic impact treatment (UIT), LSP and water jet cavitation peening (WJCP) at introducing residual stresses and modifying the near surface state compared to SP benchmark for AISI 304. It was concluded that WJCP and LSP introduced the lowest levels of surface roughening.…”
Section: Introductionsupporting
confidence: 82%
“…It was noteworthy that the maximum compressive stresses in the longitudinal direction for both butt joint and T-joint were relatively higher than the compressive limit of 304L steel, which implied cold working by the UIT induced plastic deformation of the weld joint. The similar level of compressive residual stresses higher than the material's yield limit was also obtained and reported by previous studies [11,28,32].…”
Section: Effects Of Uit On Weld Residual Stressessupporting
confidence: 65%
“…In most of the cases, it has been found that the UIT introduces compressive residual stresses along varying depths and improves fatigue performances of weld joints in various extent. Turski et al [11] found that the UIT produced compressive residual stress fields of about 2 mm in depth for 304 stainless steel. Liu et al [12] measured residual stresses of UIT-treated high strength steel weld joints.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations